Towards a new frramework for financial stability - Mayes, David; Pringle, Robert; Taylor, Michael (United Kingdom: Central Banking Publications Ltd., 2009)
This book presents a large number of important studies which help to explain the background and origins of the crisis, its development over time and potential measures to prevent its recurrence or at least to mitigate the probability of recurrence.
Includes index.
rua 23/02/17
Loans.
Keywords: Monetary policy; Banks and banking - international; Economic stabilization; Financial crisis; International finance; International finance - law and legislation